PENETAPAN STANDARISASI NON SPESIFIK EKSTRAK ETANOL HASIL PERKOLASI UMBI BAWANG DAYAK (Eleutherine palmifolia (L.)Merr) - Dyan Wigati; Ryan Radix Rahardian (Universitas Wahid Hasyim Semarang, 2018)
ABSTRACTDayak Onion (Eleutherine palmifolia (L.) Merr) is known to have several benefits including treating cancer, hypertension, lowering cholesterol. This study aims to determine the non-specific parameters of ethanol extract from Dayak onion bulbs which include drying shrinkage parameters, moisture content, ash content, acid insoluble ash content. Extraction was carried out percolation with 96% ethanol and yielded a yield of 12.44%. Dayak onion tuber extract was thick with a distinctive smell of onion and reddish brown color. The contents of the active compounds include flavonoids, saponins, tannins, alkaloids and quinones. The results showed a shrinkage value of 9.73 ± 0.10%, moisture content 9.42 ± 0.36% ash content 4.83 ± 0.27% and acid insoluble ash content 0.45 ± 0.49Keywords: Dayak Onion, 96% ethanol extract, non specific parameters